One Health-ness Evaluation of Cysticercosis Surveillance Design in Portugal - Fonseca, Ana Gloria; Torgal, Jorge; de Meneghi, Daniele; Gabriël, Sarah; Coelho, Ana Cláudia; Vilhena, Manuela (Frontiers in Public Health, 2018)
The increasing occurrence of human cysticercosis, a zoonotic neglected disease, is challenging the traditional prevention and control paradigm and calling for One Health (OH) solutions in industrialized countries. OH solutions for health interventions are increasingly being used to capture expected and unexpected outcomes across people, animals and the environment. The Network for One Health Evaluation (NEOH) proposes an evidence-based framework, relying on systems and mixed methods approaches to evaluate the One Healthness. In this case study, this tool is used to evaluate the design of the Observatory of Taeniasis and Cysticercosis, as an example of inter-sectorial collaboration for surveillance in Portugal. The OH initiative (drivers, expected outcomes) and its system (boundaries, aim, dimensions, actors, stakeholders) were described. The different aspects of this initiative were scored with values from 0 (=no OH approach) to 1 (=perfect OH approach). The OH index was 0.31. Its OH ratio is 1.98. Overall scores were: OH thinking 0.75; OH planning 0.60; OH working 0.60; OH sharing 0.35; OH learning 0.50 and Systemic organization 0.50. Operational levels of the Initiative are the main strengths, indicating a comprehensive multidimensional innovative approach and transdisciplinarity. Critical issues in the supporting infrastructure were observed, related to communication, learning and organizational gaps in the project, with the evaluation being conducted as the project is being designed and implemented. The strengths and weaknesses detected may be used to refine the initiative. This case study therefore exemplifies and supports OH assessment also for ongoing projects, at design and early implementation stages for guiding and guaranteeing a OH oriented perspective.